Rol de la biopsia por aspiración con aguja fina (BAAF) en el abordaje diagnóstico de tumoraciones mamarias palpables en el Instituto Nacional de Enfermedades Neoplásicas, Lima-Perú - Maita Cruz, Yuri Anselmo (2018)
Objective: The objective of the study was to determine if fine-needle aspiration biopsy is a safe method to diagnose breast cancer in women with a palpable breast tumor. Materials and methods: A prospective, analytical and cross-sectional study on cancer prevention conducted in 105 women with a palpable breast tumor who went to the Department of Cancer Prevention and Diagnosis of the Instituto Nacional de Enfermedades Neoplásicas (INEN) from July 1, 2014 to April 30, 2015. The study sample was selected through non-probabilistic sampling, and based on inclusion and exclusion criteria. Results: The average age was significantly higher in the group with a malignant pathological result (51.21 years). It was observed that, as age increases, benign pathologies decrease in frequency in comparison with malignant pathologies that increase in frequency. It was also observed that out of the total of 105 women with a palpable tumor, 35.2% had a malignant pathology and 64.8% had a benign pathology. Sensitivity, specificity, positive predictive value, and negative predictive value were estimated at 94%, 96%, 94% and 96%, respectively. The diagnostic safety of the FNAB was 90.3%. Conclusions: Fine-needle aspiration biopsy is a safe diagnostic method for the detection of breast cancer in women with palpable breast tumors.